(untitled) (African Human Mobility Review, 2021)
This paper presents qualitative data from two independent studies on South African attitudes towards immigrants and European immigration to South Africa, respectively. The data demonstrate that many South Africans perceive Europeans to be unproblematic and even contribute to the country, and that European immigrants in Johannesburg enjoy a privileged experience of immigration, especially as compared to their African counterparts. The visible outcomes of European privileges such as international mobility and access to resources accumulated in and by European states, contextualised in experiences and legacies of the Apartheid regime, are reflected in perceptions of European immigrants in South Africa. Moreover, perceptions of European immigrants shape their privileged experience and enable their social mobility in a deeply segregated country by exempting them from migration politics and xenophobia and facilitating their economic integration.